From Wells to Wellness: An Introduction to Drinking Water Systems in Florida: FE1156, 10/2024 - Weng, Weizhe; Albertin, Andrea; Zhuang, Yilin (EDIS, 2024)
Safe drinking water is a fundamental requirement for human health and well-being. This publication is part of an EDIS series that aims to illuminate the critical issues surrounding drinking water quality and Florida’s drinking water system. In this article, we begin with a brief introduction to the different categories of Florida’s drinking water system. Then, we discuss relevant federal and state level regulations for each category. Information sources and channels are provided for readers to access drinking water information in their communities. The content is designed to benefit a diverse audience, including researchers, communications and outreach experts, environmental professionals, healthcare providers, and policymakers. It seeks to clarify the facts and regulatory framework governing drinking water systems, identify areas that require targeted extension programs, and aid in the development of outreach materials to ensure the provision of safe drinking water.